Body as subject() - MEIR, IRIT (2007)
The notion of subject in human language has a privileged status relative to other arguments. This special status is manifested in the behavior of subjects at the morphological, syntactic, semantic and discourse levels. Here we bring evidence that subjects have privileged status at the lexical level as well, by analyzing lexicalization patterns of verbs in three different sign languages. Our analysis shows that the sublexical structure of iconic signs denoting state of affairs in these languages manifests an inherent pattern of form–meaning correspondence: the signer’s body consistently represents one argument of the verb, the subject. The hands, moving in relation to the body, represent all other components of the event – including all other arguments. This analysis shows that sign languages provide novel evidence in support of the centrality of the notion of subject in human language. It also solves a typological puzzle about the apparent primacy of object in sign language verb agreement, a primacy not usually found in spoken languages, in which subject agreement ranks higher. Our analysis suggests that the subject argument is represented by the body and is part of the lexical structure of the verb. Because it is always inherently represented in the structure of the sign, the subject is more basic than the object, and tolerates the omission of agreement morphology.